Pemantau Lalu Lintas dengan Sensor LDR Berbasis Mikrokontroler ATmega16 - Adam Vrileuis (Universitas Syiah Kuala, 2013)
This system was designed to monitor the condition of traffic by measuring the speed and density of vehicles on the road. This system uses Light Dependent Sensor (LDR) that can detect the vehicles when there is no light stimulus. Light Dependent Sensor is used as a switch in the circuit. When the light on the sensor is blocked, it provides a response to microcontroller to turn on and turn off the timer, and to run the counter. Theoretically, the condition of traffic flow, such as traffic jams, can be indicated on the vehicle speed and density. The speed and density data were processed by microcontroller using C programming for RISC AVR (Alf and Vegard’s RISC) processor. Timing data obtained from the timer and counter were computed by applying arithmetic process to describe the traffic condition. Kinematics theory was applied to find the speedy by multiplying the distance between the sensors which was determined when the vehicles passing the sensors. This system is able to detect congestion at a road if the speed is lower and the density is higher than the setup values.